Elder abuse and victims with disabilities - Giannouli, Vaitsa (Victimology, 2022)
Elder abuse has received increasing attention worldwide as a common problem with serious consequences for older people. This chapter has two sections: the first section deals with elder abuse and the second section focuses on elder victims with disabilities. Many different forms of elder abuse are reported, with a consensus regarding physical abuse, psychological/emotional abuse, sexual abuse, neglect, self-neglect, abandonment, and financial/material exploitation, which are described in detail. The cases and risk factors, victim experiences, and the social and policy impacts will be discussed. The second section is about elder victims with physical and intellectual disabilities and other related disabilities who are also very vulnerable to crimes. Risk factors and victim experiences will be explored. Prevention, intervention and rehabilitation methods will be described for both sections, with an extended discussion regarding methodological issues, which need to be considered when conducting relevant research.